THE ROLE OF LEARNING ABILITY AND MORALITY IN AVOIDING BULLYING BEHAVIOR AMONG 7TH GRADE STUDENTS AT MTS AHMAD YANI, WONOTUNGGAL, BATANG REGENCY - Rahma Ihza Zenobia; Abdul Majid; Nurfarida (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2026)
This study was motivated by the continued presence of bullying behavior at MTs Ahmad Yani Wonotunggal and the gap between the learning objectives of Akidah Akhlak and the reality of student behavior. Research objectives: (1) to describe the characteristics of bullying behavior among seventh-grade students, (2) to analyze the implementation of Akidah Akhlak instruction, and (3) to identify the role of Akidah Akhlak instruction in preventing bullying. The study employed a descriptive qualitative approach. Data collection techniques included observation, interviews, and documentation. Research subjects included Akidah Akhlak teachers, seventh-grade students, homeroom teachers, and the madrasah principal. Data analysis utilized the Miles and Huberman model, and data validity was tested through source and method triangulation. Research findings: (1) Bullying behavior is predominantly verbal (taunting, negative nicknames) and social (mild exclusion, gossip). Causal factors include individual factors (low self-control, lack of empathy), family (inadequate parenting, low supervision), school (weak supervision, lack of a reporting system), and peers (conformity pressure). (2) The implementation of Akidah Akhlak instruction has been in accordance with Ministerial Decree No. 183 of 2019, featuring relevant content on praiseworthy and blameworthy moral conduct; however, the teaching method remains predominantly lecture-based, and assessment focuses primarily on cognitive aspects. (3) The role of Akidah Akhlak education is quite effective in the cognitive aspect (students understand the prohibition of bullying in Islam), but limited in the affective aspect (empathy is normative) and minimal in the psychomotor aspect (no training in skills to refuse or report bullying). Teachers act as role models, dialogue facilitators, and spiritual counselors, but lack systemic support from the school. Akidah Akhlak education plays a role but is not yet optimal in preventing bullying; therefore, strengthening of methods, evaluation, and collaboration among school stakeholders is needed.